Green Banking, Profitabilitas, dan Usia Perusahaan Sebagai Determinan Nilai Perusahaan pada Bank Umum Syariah di Bursa Efek Indonesia - Aninda Merliana Putri; Novi Mubyarto; Rohana Rohana (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This research aims to analyze the influence of green banking, profitability, and firm age on firm value in Islamic Commercial Banks (Bank Umum Syariah/BUS) listed on the Indonesia Stock Exchange (BEI), considering the importance of sustainability practices and financial performance in shaping investor perception. The research sample consists of four BUS selected using a purposive sampling technique, with annual data for the 2014–2024 period forming an unbalanced panel which was analyzed using panel data regression via EViews 12. The results show that green banking (proxied by the Green Banking Disclosure Index/GBDI) has a significant positive influence, serving as a signal that enhances the market's valuation of the firm. Conversely, Profitability (ROA) has no significant influence, indicating that a high level of profitability is not yet the primary determinant factor for market perception. Meanwhile, Firm Age has a significant positive influence, confirming that long-term experience and credibility increase investor confidence and firm value. Simultaneously, all three variables are proven to have a significant influence on firm value. These findings emphasize that both the aspect of sustainability and the firm's operational experience are important factors in the determination of firm value.